OBSERVASI LINGKUNGAN SEKOLAH DAN IMPLEMENTASI KEGIATAN PEMBELAJARAN DALAM PROGRAM PENGENALAN LAPANGAN PERSEKOLAHAN (PLP) DI HANG ISLAMIC SCHOOL BATAM - Sakina Auxalery, Tasya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Field Introduction Program (PLP) at Hang Islamic School Batam. The method used is descriptive qualitative through direct observation and participation in school activities. The results show that the school environment is clean, conducive, and supports the learning process. Learning activities such as tahfidz and basic literacy (reading, writing, arithmetic) are implemented effectively using repetition and gradual approaches according to children's development. In addition, administrative activities provide practical experience for students in managing school data. Overall, the PLP program provides meaningful learning experiences in understanding real educational practices in schools.